Pengaruh Kompensasi dan Motivasi Terhadap Kinerja Kader KB di Desa Campaka Mekar - Yudhanegara, Darmawan; Nusantara Dwi Setyo (Sekolah Tinggi Teknologi Wastukancana, 2024)
This research investigates the influence of compensation and motivation on the performance of Family Planning (KB) cadres in Campaka Mekar Village. KB cadres play a vital role in disseminating information and services at the community level, but they often face challenges related to minimal compensation and low motivation. This study uses a quantitative method with 30 respondents of KB cadres in Campaka Mekar Village. The results of the analysis using Smart PLS 3 show that compensation has a significant positive effect on the performance of KB cadres, while motivation does not have a significant effect. This indicates the need to increase compensation as a strategy to improve the performance of KB cadres. This research provides insights for the development of more effective policies in the implementation of KB programs at the village level. Research result that impact to performance from compansation of 0.907